2007
DOI: 10.1007/s00432-006-0188-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin lymphoma with t(14;18): clonal evolution patterns and cytogenetic–pathologic–clinical correlations

Abstract: Secondary chromosomal aberrations showed some correlation with the morphologic subgroups of t(14;18)-NHL. Trisomy 21 and the presence of >6.0 secondary cytogenetic aberrations both correlated with shorter overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Triple hit lymphomas were mostly represented by combinations of the t(8;22)(q24;q11) and a t(14;18)(q32;q21) (six of eight cases) (Stamatoullas et al, 2000;Henderson et al, 2004;D'Achille et al, 2006;Le Gouill et al, 2007;Johnson et al, 2009); one case had a t(2;8)(p12;q24) and t(18;22)(q21;q11) in combination (Au et al, 1999), and one case had both a t(8;14)(q24;q32) and t(14;18)(q32;q21) additionally to a BCL6 rearrangement (Aamot et al, 2007). No cases with four hits involving BCL6, MYC, BCL2, and CCND1 as reported in this study were found in the Mitelman database.…”
Section: Search Of the Mitelman Databasementioning
confidence: 96%
“…Triple hit lymphomas were mostly represented by combinations of the t(8;22)(q24;q11) and a t(14;18)(q32;q21) (six of eight cases) (Stamatoullas et al, 2000;Henderson et al, 2004;D'Achille et al, 2006;Le Gouill et al, 2007;Johnson et al, 2009); one case had a t(2;8)(p12;q24) and t(18;22)(q21;q11) in combination (Au et al, 1999), and one case had both a t(8;14)(q24;q32) and t(14;18)(q32;q21) additionally to a BCL6 rearrangement (Aamot et al, 2007). No cases with four hits involving BCL6, MYC, BCL2, and CCND1 as reported in this study were found in the Mitelman database.…”
Section: Search Of the Mitelman Databasementioning
confidence: 96%
“…The karyotypes of the first biopsies from 40 of these patients have been published previously. 36 aCGH and statistical considerations DNA was isolated from frozen tissue with the use of the EZ1 tissue kit (QIAGEN). DNA copy number alterations (CNAs) were detected by aCGH on in-house arrays containing approximately 4500 Bacterial Artificial Chromosomes/P1-derived Artificial Chromosomes (BAC/PACs) in quadruplicate at an average resolution of 1 megabase.…”
Section: Patients and Biopsiesmentioning
confidence: 99%
“…Weisenburger et al () showed an association between trisomy 21 and poor survival that was independent of t(14;18) in follicular large cell lymphoma. Aamot et al () showed that both trisomy 21 and the presence of more than six secondary cytogenetic aberrations correlated with a shorter OS in FL. However, these results were obtained from patients in whom the treatments were unknown or who were not treated with rituximab (Yunis et al , ; Weisenburger et al , ; Aamot et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Aamot et al () showed that both trisomy 21 and the presence of more than six secondary cytogenetic aberrations correlated with a shorter OS in FL. However, these results were obtained from patients in whom the treatments were unknown or who were not treated with rituximab (Yunis et al , ; Weisenburger et al , ; Aamot et al , ). To our knowledge, only one report mentioned that patients with 6q‐ had a shorter OS in an R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone)‐like treatment group (Tsukamoto et al , ).…”
Section: Discussionmentioning
confidence: 99%